2012
DOI: 10.1590/s0102-79722012000300017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selection tasks on naming emergence in children

Abstract: The aim of the present work -which was divided into two studies -was to investigate if, from teaching selection tasks, naming responses would be emitted without direct teaching. Nine children aged between 7 and 12 participated in the study. In each study, 12 abstract pictures and 12 pseudo words were utilized. The procedures were comprised of six sessions that encompassed selection tasks (name-picture relations) and naming tests (picture-name relations). When a participant met 100% correct responses in selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
8

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 21 publications
1
2
0
8
Order By: Relevance
“…During the initial evaluation, the participants of this study presented distinct percentages of correct responses between the speaker's behavior (tact and echoic) and the listener's (listening based on selection). These results are one more evidence, among many reported in literature, of the functional independence between the repertoire of listener and speaker in different populations, such as typical listener children (11) , with Down Syndrome (3) , with intellectual disability and with neurosensory hearing loss and CI (26) .…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…During the initial evaluation, the participants of this study presented distinct percentages of correct responses between the speaker's behavior (tact and echoic) and the listener's (listening based on selection). These results are one more evidence, among many reported in literature, of the functional independence between the repertoire of listener and speaker in different populations, such as typical listener children (11) , with Down Syndrome (3) , with intellectual disability and with neurosensory hearing loss and CI (26) .…”
Section: Discussionsupporting
confidence: 55%
“…At the listener's tasks, a dictated word was presented as sample and three pictures as comparison and the participant selected the picture (comparison stimuli) that was arbitrarily related to the auditory sample. The results in the different studies suggest that learning listener's behaviors was not condition for the naming to occur, even in the conditions where the echoic was accurately issued in the pre-tests (11) . On the other hand, other studies have demonstrated the biderectional relation between the listener's and speaker's behavior (13) , including children with hearing loss and CI (14) .…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Considerando os diferentes procedimentos de ensino dos comportamentos de ouvinte e de falante, há estudos que utilizam tarefas de seleção e nomeação dos operantes verbais mando e tato com diferentes populações e em diferentes idades (Anastácio-Pessan, Almeida-Verdu, Bevilacqua, & Souza, 2015;Arntzen & Almas, 2002;Bandini, Sella, Postalli, Bandini, & Silva, 2012;Carroll & Hesse, 1987;Gomes, Benitez, Domeniconi, & Almeida-Verdu, 2017;Gurteen, Horne, & Erjavec, 2011;Hussein, Góes, Chiodelli, Silva-Marinho, Gonçalves, & Almeida-Verdu, 2018;Lamarre & Holland, 1985;Petursdottir, Carr, & Michael, 2005;Santos, Neves, Silva, & Almeida-Verdu, 2014;Santos & Souza, 2016;Sousa, Souza, & Gil, 2013). Alguns desses estudos utilizaram o procedimento de emparelhamento de acordo com modelo (matching to sample) para o ensino de discriminação condicional auditivo-visual (entre pseudopalavras e figuras abstratas) e testaram a nomeação das figuras, apresentando uma a uma.…”
Section: Direitos Autoraisunclassified
“…Trabalhando com uma idade menor, se comparado à faixa etária dos participantes do estudo de Bandini et al (2012), e com um procedimento de ensino semelhante ao empregado por Bandini et al (2012), no estudo de Sousa et al (2013), investigou-se os efeitos da combinação dos procedimentos de emparelhamento simultâneo de um estímulo auditivo e um estímulo visual e de emparelhamento com o modelo sobre a aprendizagem de comportamento de ouvinte por um bebê de 17 meses. Nas sessões de linha de base, a experimentadora selecionou algumas figuras de um livro infantil e, posteriormente, solicitou que a bebê as nomeasse.…”
Section: Direitos Autoraisunclassified